The right to public space during the COVID-19 pandemic: A tale of rising inequality and authoritarianism in Athens, Greece. Issue 5 (2nd November 2021) - Apostolopoulou, Elia; Liodaki, Danai
Abstract : Governmental policies to combat the spread of the novel coronavirus (SARS-CoV-2) have directly and decisively intervened with literally every facet of people's life transforming the geographies of everyday lives across the Global South and North. In this paper, we explore the shifting relationship of urban dwellers to public space during the COVID-19 pandemic with the aim to unravel the uneven ways lockdown measures and restrictions on movement have impacted the residents of Athens, the capital of Greece. By focusing on the way the relationship of different social groups to public space has been affected by governmental measures, we show how the reconfiguration of the production of urban public space has disproportionately affected people along lines of class, ethnicity and gender. We argue that governmental measures have so far deepened systemic inequality, segregation and social, spatial and environmental injustice in the city and have imposed unprecedented restrictions in people's democratic rights, consolidating a shift towards a more authoritarian version of neoliberal urbanism. By opposing and challenging the possibility of only dystopian futures that has dominated public discourse and collective imagination within this ongoing global public health crisis, we address a call to radical scholars and activists to start envisaging possibilities for a plural use of space and a new undisciplined, radical politics of coexistence in shared, safe spaces along the lines of a geography of togetherness, care and resistance.